Intrapartum Fetal Electrocardiogram in Small- and Large-for-Gestational Age Fetuses - Braginsky, Lena; Weiner, Steven J.; Saade, George R.; Varner, Michael W.; Blackwell, Sean C.; Reddy, Uma M.; Thorp, John M., Jr.; Tita, Alan T.N.; Miller, Russell S.; McKenna, David S.; Chien, Edward K.S.; Rouse, Dwight J.; El-Sayed, Yasser Y.; Sorokin, Yoram; Caritis, Steve N.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development Maternal-Fetal Medicine Units (MFMU) Network (American Journal of Perinatology, 2021)
Objective This study aimed to evaluate whether intrapartum fetal electrocardiogram (ECG) tracings with ST-elevation or depression occur more frequently in each stage of labor in small-for-gestational age (SGA) or large-for-gestational age (LGA), as compared with appropriate-for-gestational age (AGA) fetuses.Study Design We conducted a secondary analysis of a large, multicenter trial in which laboring patients underwent fetal ECG waveform-analysis. We excluded participants with diabetes mellitus and major fetal anomalies. Birth weight was categorized as SGA (<10th percentile), LGA (>90th percentile), or AGA (10–90th percentile) by using a gender and race/ethnicity specific nomogram. In adjusted analyses, the frequency of ECG tracings with ST-depression or ST-elevation without depression was compared according to birthweight categories and labor stage.Results Our study included 4,971 laboring patients in the first stage and 4,074 in the second stage. During the first stage of labor, there were no differences in the frequency of ST-depression in SGA fetuses compared with AGA fetuses (6.7 vs. 5.5%; adjusted odds ratio [aOR]: 1.41, 95% confidence interval [CI]: 0.93–2.13), or in ST-elevation without depression (35.8 vs. 34.1%; aOR: 1.17, 95% CI: 0.94–1.46). During the second stage, there were no differences in the frequency of ST-depression in SGA fetuses compared with AGA fetuses (1.6 vs. 2.0%; aOR: 0.69, 95% CI: 0.27–1.73), or in ST-elevation without depression (16.2 vs. 18.1%; aOR: 0.90, 95% CI: 0.67–1.22). During the first stage of labor, there were no differences in the frequency of ST-depression in LGA fetuses compared with AGA fetuses (6.3 vs. 5.5%; aOR: 0.97, 95% CI: 0.60–1.57), or in ST-elevation without depression (33.1 vs. 34.1%; aOR: 0.80, 95% CI: 0.62–1.03); during the second stage of labor, the frequency of ST-depression in LGA compared with AGA fetuses (2.5 vs. 2.0%, aOR: 1.36, 95% CI: 0.61–3.03), and in ST-elevation without depression (15.5 vs. 18.1%; aOR: 0.83, 95% CI: 0.58–1.18) were similar as well.Conclusion The frequency of intrapartum fetal ECG tracings with ST-events is similar among SGA, AGA, and LGA fetuses.Key Points
Keywords: fetal ECG; small-for-gestational age; fetal growth restriction; large-for-gestational age; ST-segment analysis; ST-events